Cerita seru panca dan sila: Inovasi buku berjenjang untuk literasi membaca - Siti Rochmiyati; Tri Nafiah (Piramida Akademi, 2026)
Literacy reading skills, especially elementary school students, are crucial aspects. However, there is still a lack of quality books, particularly at the C level (Semenjana). The purpose of this research is to create a tiered storybook with Pancasila Student Profile content in digital and print formats. The research method used is a research and development (R&D). The research subjects consist of 21 school principals, 5 teachers, and 10 fifth-grade students from several elementary schools in Moyudan District, Sleman, Yogyakarta. Data were collected through questionnaires, interviews, observations, and documentation. Data analysis was conducted descriptively qualitatively and quantitatively. The result of this research is an analysis of the needs that are suitable for students' needs to create a tiered storybook product named